Evaluation of in-vivo model for vitamin A bioavailability from vitamin A loaded caseinate complex. (August 2021) - Rana, Seema; Arora, Sumit; Gupta, Chitra; Bodemala, Harisha; Kapila, Suman
Abstract: Chemical instability of vitamin A (VA) against acidic pH is the major cause for its low bioavailability. Hence, to improve VA bioavailability, native and modified sodium caseinate were used as delivery system and evaluated for VA bioavailability through in-vivo trials. Effect of VA supplementation through native and modified sodium caseinate-VA complex fortified milks over 4 weeks was monitored in rats. The important VA bioavailability indicators i.e., body weight gain, serum and liver retinol levels, haematological parameters, apparent digestibility coefficient and % retention were investigated. Body weight gain, apparent digestibility coefficient and % retention improved significantly on VA supplementation through milk protein-VAcomplexes. Serum and liver retinol levels were highest in RNaCas followed by NaCas, SNaCas, RSNaCas and free VA fed groups. During the formation of RNaCas and RSNaCas, hydrophobic sites, buried in deep were exposed leading to binding of VA on interior hydrophobic regions of sodium caseinate molecule. Binding of VA with hydrophobic amino acid groups provided protection and stability to VA which may decrease exposure of VA to acidic pH due to its binding on the antioxidative bioactive peptides generated during gastric digestion. Thus, higher stability improved the in-vivo bioavailability of VA. Graphical abstract: Image 1 Highlights: Casein provided protection to VA, leading to improved vitamin A status in complex fortified milk fed rats. Higher serum retinol concentration was observed in complex fortified milk fed rats. Complex improved the vitamin A bioavailability as apparent digestibility coefficient and retention % was higher in complex fed rats. Modified complexes improved the vitamin A bioavailability as compared to native sodium caseinate complex.